Alternative codends to reduce bycatch in Chilean crustacean trawl fisheries - Queirolo, Dante (2016)
This study was conducted to determine the reduction in bycatch and the loss of target catch in trawl hauls for three commercial crustacean species (yellow squat lobster, Cervimunida johni, nylon shrimp, Heterocarpus reedi, and red squat lobster, Pleuroncodes monodon) in central Chile. Two experiments were carried out using the covered codend method; the first used different mesh sizes (56 and 70 mm, knot-centre to knot-centre) and shapes (diamond and square), and the second tested different reduction devices (escape panel and sorting grid). We analysed the escape proportions of the species caught and the size frequency distributions of the target species and Chilean hake (Merluccius gayi), the main commercial bycatch species. The results demonstrate that it is feasible to significantly reduce bycatch while keeping losses within acceptable ranges. In particular, the best option for yellow squat lobster was the combination of a 70-mm diamond mesh with an escape panel that reduced non-target and target catches by 48% and 7%, respectively. For nylon shrimp, the best option was the use of a 56-mm diamond mesh with a sorting grid that reduced non-target and target catches by 41% and 11%, respectively. Although the results for red squat lobster were not as promising, they will help to guide future research.